Peran dan pengaruh kecerdasan buatan (AI) dalam bidang pendidikan di Indonesia - Ba'Alawy, Quthbuddin Muhammad (Maliki Interdisciplinary Journal, 2025)
The presence of AI can also enhance and instill independence in students. An important effort in preparing students for Indonesia Emas is recognizing the rapid development of technology today, which has advanced significantly and influenced all aspects of life, especially in the field of education. One of these technological advancements is AI (Artificial Intelligence), which has been applied in education across various countries over the past few years. AI is a system designed to be innovative in research domains and can be replicated on machine devices or computers. The purpose of creating this journal is to understand the role and influence of AI in the teaching and learning system in schools and within Indonesia’s education sector. The utilization of artificial intelligence in education can facilitate school learning by developing skills in an effective and efficient manner. Although AI has great potential in learning, it also presents challenges such as data security, privacy issues, and the fact that it cannot replace the role of teachers in the learning process. Therefore, AI is not a substitute but rather a supporting tool that makes learning easier, more practical, and more efficient. The field of artificial intelligence also has a significant impact on curriculum design and teaching methods in educational institutions. Thus, the role of AI is highly needed to support the progress and development of Indonesia’s education system.